2010
DOI: 10.1245/s10434-010-1319-2
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Intraperitoneal Chemotherapy with Mitomycin C on the Prevention of Peritoneal Recurrence in Colorectal Cancer Patients with Positive Peritoneal Lavage Cytology Findings

Abstract: It appears that IPC with MMC is an effective treatment to prevent peritoneal recurrence and prolong the cancer-specific survival in CRC patients without peritoneal dissemination, but who have positive peritoneal lavage cytology. It is necessary to verify the effectiveness of IPC with MMC in a prospective trial.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(43 citation statements)
references
References 33 publications
0
42
0
1
Order By: Relevance
“…Simultaneous use of CRS and HIPEC as part of the primary cancer treatment has been associated with favorable results [6][7][8][9]. It is also the focus of two active clinical trials [10,11].…”
Section: Patients To Be Included In This Clinical Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…Simultaneous use of CRS and HIPEC as part of the primary cancer treatment has been associated with favorable results [6][7][8][9]. It is also the focus of two active clinical trials [10,11].…”
Section: Patients To Be Included In This Clinical Pathwaymentioning
confidence: 99%
“…A positive cytology may also be considered an adequate cause for secondlook HIPEC. Patients with positive cytology prior to or after primary colorectal cancer resection have an incidence of peritoneal metastases of 50% (Table 1) [9].…”
Section: Other Clinical Features That May Require a Second-look With mentioning
confidence: 99%
“…Various investigators have reproposed this strategy particularly in patients with free endoperitoneal cancer cells [75,76]. In 2014 Sloothaak et al [77] published a systematic review evaluating the main experiences in preventing endoperitoneal spread in advanced colorectal cancer with proactive endoperitoneal chemotherapy.…”
Section: Proactive Management Of Peritoneal Metastases From Colorectamentioning
confidence: 99%
“…The comparative study was nonrandomized, and no difference in OS was observed. In another uncontrolled study, a group of CRC patients with positive cytology at the time of primary resection were selected for postoperative IP administration of mitomycin C. In a multivariate analysis, IP-CHT was the only significant prognostic factor for peritoneal recurrence survival, even though OS was not affected by the locoregional treatment [82]. These studies show that an aggressive prophylactic surgical approach associated with IP-CHT may positively modify the natural course of peritoneal disease and be of benefit in selected Table 19.…”
Section: Prophylactic Hipecmentioning
confidence: 99%